Predictors of type 2 diabetes remission in the Diabetes Remission Clinical Trial (DiRECT). Issue 8 (27th September 2020) - Thom, G.; Messow, C.‐M.; Leslie, W. S.; Barnes, A. C.; Brosnahan, N.; McCombie, L.; Al‐Mrabeh, A.; Zhyzhneuskaya, S.; Welsh, P.; Sattar, N.; Taylor, R.; Lean, M. E. J.
Abstract: Aim: To identify predictors of type 2 diabetes remission in the intervention arm of DiRECT (Diabetes Remission Clinical Trial). Methods: Participants were aged 20–65 years, with type 2 diabetes duration of <6 years and BMI 27–45 kg/m 2, and were not receiving insulin. Weight loss was initiated by total diet replacement (825–853 kcal/day, 3–5 months, shakes/soups), and weight loss maintenance support was provided for 2 years. Remissions (HbA1c <48 mmol/mol [<6.5%], without antidiabetes medications) in the intervention group ( n = 149, mean age 53 years, BMI 35 kg/m 2 ) were achieved by 68/149 participants (46%) at 12 months and by 53/149 participants (36%) at 24 months. Potential predictors were examined by logistic regression analyses, with adjustments for weight loss and effects independent of weight loss. Results: Baseline predictors of remission at 12 and 24 months included being prescribed fewer antidiabetes medications, having lower triglyceride and gamma‐glutamyl transferase levels, and reporting better quality of life with less anxiety/depression. Lower baseline HbA1c was a predictor at 12 months, and older age and male sex were predictors at 24 months. Being prescribed antidepressants predicted non‐remission. Some, but not all effects were explained by weight loss. Weight loss was the strongest predictor of remission at 12 months (adjusted odds ratio per kg weight loss 1.24, 95% CI 1.14, 1.34; P < 0.0001) and 24 months (adjusted odds ratio 1.23, 95% CI 1.13, 1.35; P <0.0001). Weight loss in kilograms and percentage weight loss were equally good predictors. Early weight loss and higher programme attendance predicted more remissions. Baseline BMI, fasting insulin, fasting C‐peptide and diabetes duration did not predict remission. Conclusions: Other than weight loss, most predictors were modest, and not sufficient to identify subgroups for which remission was not a worthwhile target.